(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aims to determine the satisfaction of tourist management at the Amaro Hotel Resort in Punturin, Valenzuela City. It aims to improve and enhance the knowledge about reaching the business’s success and how effective the management is. This study used the Expectation Confirmation Theory of Customer Satisfaction. The theory mentioned is quite relevant in this study as it implies the concept of expectations, which relates to one of the variables cited in this study (performance). Also, this study implies the concept of Customer Satisfaction. The study utilized a descriptive research method and a purposive sampling where the researchers focused on fifty (50) customers of Amaro Hotel Resort and created Three (3) parts to the survey questionnaire that are based on the problem of the studies. The researcher uses frequency and percentage to determine the respondents and the description according to age, gender, economic status, and income status. Weighted means assessing the satisfaction of tourist management in terms of price, performance, place, and promotion. Analysis of variance (ANOVA) for hypothesis testing. The conspicuous findings of the percentage status found that 76% of 50 respondents aged 20-29 are mostly male. Most tourist customers who visit the Amaro Hotel Resort are employed and have an income status of 0-999 pesos. The respondents assess tourist management satisfaction regarding product, place, performance, and promotion. The respondents imply a significant relationship between the profile and the variables mentioned above. Since the total P-value is 0.1155, it is less than the tabular or critical value of 3.182 at the significance level = 0.05. it is significant and, therefore, accepted the hypothesis. The customers concurred on assessing the factors or variables of tourist satisfaction in terms of price and that the option for payment method is the best for concentration. In terms of performance, online transactions with the resorts are the best choice. At the same time, the comfort of the place for the customer is most important, and for promotion, using social media for their advertisement is most convenient to surf and use. A significant relationship exists between the profile and the variables mentioned in their business customer satisfaction. By all counts, and with the proven result, it is no wonder that limited customer capacity and cheap food and beverages are the main problems facing customers. It will inform them about the minor problems that the tourist customer encountered.